2018
DOI: 10.1111/jan.13769
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Pap smear uptake in a maternity hospital: A descriptive cross‐sectional study

Abstract: Various factors were found to influence Pap smear uptake. Future interventions can take these factors into account for increasing Pap smear awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
0
12
1
1
Order By: Relevance
“…The final multivariate model accounted for 31% of the variance of intention to undergo Pap smear testing. The variance in the current study is higher than that in one previous study from Singapore, which only explains 20.4% variance [ 38 ]. However, the final block containing health belief variables only explained 5% of the variance of intention to undergo Pap smear testing.…”
Section: Discussioncontrasting
confidence: 83%
“…The final multivariate model accounted for 31% of the variance of intention to undergo Pap smear testing. The variance in the current study is higher than that in one previous study from Singapore, which only explains 20.4% variance [ 38 ]. However, the final block containing health belief variables only explained 5% of the variance of intention to undergo Pap smear testing.…”
Section: Discussioncontrasting
confidence: 83%
“…Of the 12 studies reporting facilitators in Singapore, five reported facilitators within the category of perception, attitude, and belief, while four described facilitators in the categories of knowledge, demographics, and healthcare utilization. Top facilitating factors were related to age [ 89 , 92 , 99 ], support from family and friends [ 88 , 89 , 92 ], good awareness of screening [ 89 , 92 , 96 ], and high perceived benefit [ 90 , 92 , 99 ]. Other top facilitators include healthcare worker advice for screening [ 89 , 92 , 96 ] and health center characteristics such as a convenient screening location [ 87 , 93 , 96 ] and the availability of female health workers or nurses for the conduct of screening [ 87 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…A majority of the studies (n = 81) were crosssectional or case-control studies, while the rest were qualitative (n = 9) or mixed-methods (n = 3) studies. Most of the studies were conducted in Malaysia (35.5%, n = 33) , followed by Thailand (24.7%, n = 23) , Indonesia (16.1%, n = 15) [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], and Singapore (15.1%, n = 14) [86][87][88][89][90][91][92][93][94][95][96][97][98][99]. None of the studies were conducted in the Philippines and Timor-Leste.…”
Section: Study Characteristicsmentioning
confidence: 99%
“… 59 In addition, one study investigated members of the church of Ireland. 55 Among other religious groups, n=4 articles included Muslims, 30 , 46 , 57 , 61 the same number examined Jewish people, 23 , 26 , 27 n=3 studies Buddhists, 30 , 57 , 61 and n=1 study Hinduists. 61 Eventually, n=7 studies explored the association between religious factors and the utilization of cancer screenings among members of other religions, 23 , 26 , 30 , 48 , 57 , 59 , 61 and n=8 studies for non-religious people.…”
Section: Resultsmentioning
confidence: 99%